RELATIONSHIP OF THE USE OF INJECTED NARCOTICS WITH HEPATITIS C COINFECTION IN TEBET Hospital, 2017-2019 - Qurratu Ayunin; Krisnawati Bantas (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2020)
Background: The number of people who was infected HIV/AIDS over the world approximately 37,9 milion in 2018. Hepatitis C coinfection in HIV patients approximately 2-15% over the world and for 90% were injecting drug users. This study aims to find the correlation injecting drug use and hepatitis C coinfection in HIV patients in RSUD Tebet from 2017-2019. Method: This study use case-control design using medical record data. We studied 186 samples and use simple random sampling for recruiting sample. Analysis of the data used SPSS software and were analyzed by univarit, bibariat, multivariat with logistic regression. Results: Injecting drug use showed a significant correlation with Hepatitis C coinfection in HIV patients with OR adjusted 12,7 (95% CI (3,8 - 42,37) and p-value 0,001 after adjusted with working status, age, sex, and risky sexual behavior. Conclution: Injecting drug use showed a significant correlation with Hepatitis C coinfection in RSUD Tebet.